Role Overload, Teacher-Pupil-Ratio, School Type, Years of Teaching Experience, Gender and Burn Out as Factors Related to Work Stress among Primary School Teachers in Kasarani Division, Nairobi County, Kenya (Global Journal of Human-Social Science, 2014)
The intention of this study was to establish the work related factors that contribute to stress and burn out among primary school teachers in Kasarani. To achieve this, the study sought to investigate the role played by overload in terms of lessons taught per week and class size. The study also explored whether school type (public or private) had any relationship with work stress. In addition the study sought to establish were years of teaching experience, gender and their relationship with work stress. Data were collected from 120 teachers through a paper based questionnaire. Majority of teacher reported work overload (50.83%) against 43.33% who reported mild overload while only 5.84% reported no overload.
Keywords: work stress; class size; role overload; burn out; primary school teacher